Optimising of operation conditions for carbon nanotube production using pyrolysis coupled with catalytic chemical vapor deposition / Mohd Syazwan Mohd Ghazali ... [et al.] - Mohd Ghazali, Mohd Syazwan; Md Zaini, Mohd Saufi; Roslan, Siti Zaharah; Syed-Hassan, Syed Shatir A. (Universiti Teknologi MARA, 2024)
Sewage sludge holds great potential for producing carbon nanotubes (CNTs) due to their abundance, renewability, and low-cost carbon source. The objective of this study is to investigate the production of CNTs through two-stage processes i.e. pyrolysis and catalytic chemical vapor deposition (CCVD) of sewage sludge-derived vapor. The central composite design (CCD) model of response surface methodology (RSM) was conducted to predict and optimise the yield of CNTs from sewage sludge vapour. The statistical results indicate that the optimal conditions are a catalyst loading of 0.5 and a temperature of 800 C. The catalyst loading has the greatest impact on CNTs yield, as evidenced by the F-value in the ANOVA. The actual CNTs yield under these optimal conditions was 30.53%, which is in close agreement with the predicted value of 33.60%. A quadratic model was employed to investigate the relationship between temperature and catalyst load on the deposition yield of CNTs. The CNTs were then characterised using Raman Spectroscopy, X-ray Diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and Transmission Electron Microscopy (TEM). The optimised CNTs had an outer diameter of 25.2 nm, and inner diameters of 3.2 nm. This research contributes to the advancement of the CNTs production from sewage sludge.